2013
DOI: 10.1136/emermed-2012-201789
|View full text |Cite
|
Sign up to set email alerts
|

Performance of emergency physicians in point-of-care echocardiography following limited training

Abstract: Emergency medicine trainees were found to be able to perform and interpret focused echocardiography reliably after a short duration of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 25 publications
4
67
0
4
Order By: Relevance
“…We chose a visual estimation of LVEF because some studies have shown its accuracy when performed by noncardiologist physicians who have received a brief training in echocardiography [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…We chose a visual estimation of LVEF because some studies have shown its accuracy when performed by noncardiologist physicians who have received a brief training in echocardiography [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Although we advocate a formal FCU rotation with vertical integration throughout the program, training need not be time or resource intensive. Short courses of FCU training have been shown to be feasible and efficient in a variety of settings with a variety of learners including internal medicine [14,15], emergency medicine [40], critical care [41] and anesthesiology residents [42]. Required components of training include basic knowledge of ultrasound principles (physics, cardiac anatomy, cardiac pathology, etc.…”
Section: The Specifics Of Fcu Training Are In the Process Of Being Dementioning
confidence: 99%
“…L'échographie est un examen de choix pour détecter un épanchement péricardique, par sa disponibilité, sa sécurité et la capacité d'évaluer la fonction cardiaque associée [22]. Il existe une bonne corrélation entre l'examen réalisé par un cardiologue et celui réalisé par un urgentiste après une formation courte [23].…”
Section: éChographie Cardiaqueunclassified